Environment and Society : A Reader - Schlottmann, Christopher, 1980- (Book collections on Project MUSE., 2017)
Environment and Society connects the core themes of environmental studies to the urgent issues and debates of the twenty-first century. In an era marked by climate change, rapid urbanization, and resource scarcity, environmental studies has emerged as a crucial arena of study. Assembling canonical and contemporary texts, this volume presents a systematic survey of concepts and issues central to the environment in society, such as: social mobilization on behalf of environmental objectives; the relationships between human population, economic growth and stresses on the planet's natural resources; debates about the relative effects of collective and individual action; and unequal distribution of the social costs of environmental degradation. Organized around key themes, with each section featuring questions for debate and suggestions for further reading, the book introduces students to the history of environmental studies, and demonstrates how the field's interdisciplinary approach uniquely engages the essential issues of the present.--Publisher's description.